Pengaruh Kompetensi dan Motivasi Terhadap Kinerja Pembimbing Klinik di Rumah Sakit - kurniawati - kurniawati; chalimah - chalimah (Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this research is to determine the influence of competence and motivation on the performance of clinical instructors. This type of research is correlative. The sample for this study was 32 clinical instructors carried out by random sampling. The data analysis technique uses the Multiple Regression analysis. The results of the study showed that competence had a positive and significant effect on the performance of clinical instructors, the motivation of clinical instructor had a positive but not significant effect on the performance of clinical instructor, the competency of clinical instructor and motivation of clinical instructor had a positive and significant effect on the performance of clinical instructor.